Feasibility Study of the Jebew Noodle Business in Tambun: An Analysis of Financial and Non-Financial Aspects - Antika, Rindi; Raissa Susilo Maharani; Farah Umayna Zahra; SelviaNuraeni; Intan Permata Sari (Lentera Ilmu Nusantara, 2025)
Noodles are made fram wheat flour, which comes from wheat plants, so noodles are widely used as a staple food that has high carbohydrates like rice. Jebew noodles vision is to “create noodles that are easily recognized by consumers, with the restaurant’s distinctive taste,” The restaurant’s mission is to “implement a comfortable, clean environment and make attractive sales”. Jebew noodles MSMEs are experiencing very rapid growth with rapid increases, th main advantage is its distinctive spicy taste which is adapted to consumer taste. To maintain growth, a more intensive online marketing and social media strategy is needed. I tis recommended to expand branches, conduct periodic finansial feasibility analysis, and automate production processes to increase efficiency and capacity in anticipating increasing market demand. In a business feasibility study, there are two aspects, namely financial aspects such as Net Present Value, Internal Rate of Return, Payback Period, Switching Value Analysis, Break Even Point.